Genetic structure of the critically endangered Red‐headed Wood Pigeon Columba janthina nitens and its implications for the management of threatened island populations. (27th November 2013) - Ando, Haruko; Ogawa, Hiroko; Kaneko, Shingo; Takano, Hajime; Seki, Shin‐Ichi; Suzuki, Hajime; Horikoshi, Kazuo; Isagi, Yuji; Fuchs, Jerome
<x xml:space="preserve">Abstract</x> The Red‐headed Wood Pigeon Columba janthina nitens is endemic to the Ogasawara Islands, an oceanic island chain located 1000 km south of the main islands of Japan. The subspecies is at high risk of extinction because of its small population size and restricted habitat range. We undertook genetic analyses of this pigeon using sequences of a portion of the mitochondrial control region and five microsatellite markers to estimate the genetic characteristics of two wild populations from the Bonin and Volcano Islands, as well as one captive breeding population. The genetic diversity of the wild individuals was exceptionally low in both the mitochondria (nucleotide diversity = 0.00105) and at the microsatellite (3.2 alleles per locus and HE = 0.12) loci. Higher numbers of microsatellite genotypes were observed in the Volcano Islands population than in the Bonin Islands population, which may be because of the relatively low impact of human disturbance. The most common mitochondrial haplotypes and microsatellite alleles observed in the two wild populations were completely fixed in the captive population. Our results suggest that the genetic diversity of the captive population needs to be increased. However, introduction of a wild individual into a captive population can lead to a decreased genetic diversity in the wild population and therefore should be done with caution. The genetic differentiation between the Bonin and the Volcano island groups was low, and the populations of the two island groups should be regarded as a single evolutionarily significant unit. However, special consideration is required for habitat conservation in the Volcano Islands, which may be functioning as a sanctuary for the Red‐headed Wood Pigeon. For the long‐term conservation of threatened bird species that live on remote oceanic islands, determination of management units considering gene flow caused by their flying capacity and maintenance of genetically suitable wild and captive populations are essential.